Generalized problematic internet use and perfectionism in portuguese university students - Maia, B. Rodrigues; Soares, M.J.; Pereira, A.T.; Marques, M.; Carvalho, F.; Macedo, A. (European psychiatry, 2021)
IntroductionAlthough there are several empirical studies exploring the relationship between problematic Internet use and personality traits, few had considered perfectionism.ObjectivesTo explore the association between generalized problematic Internet use and perfectionism.MethodsA sample of 433 Portuguese university students (Mage = 20.15 years, SD = 1.77, range = 18-25 years) completed the Generalized Problematic Internet Use Scale 2/GPIU and the Multidimensional Perfectionism Composite Scale – short version.ResultsGPIU total score (rs=.16**), Mood Regulation (rs=.22**), and Deficient Self-Regulation (rs=.13**) were correlated with Positive Striving factor. GPIU total score (rs=.38**), Preference for Online Social Interaction (rs=.16**), Mood Regulation (rs=.28**), Deficient Self-Regulation (rs = .33**), and Negative Consequences (rs=.41**) were significantly correlated with Evaluative Concerns factor. A one-way between groups analysis of variance was conducted to explore the relation between GPIU and perfectionism. Subjects were divided into three groups according to their GPIU risk levels (Group1:low-risk; Group2:medium-risk; Group3:high-risk). There was a statistically difference at p >.05 level in Positive Striving scores for the three risk level groups: F (2,430)=4.39, p=.013, and in Evaluative Concerns scores, F (2,430)=28.83, p=<.001. Post-hoc comparisons using the Tukey USD test, for Positive Striving, indicated that the mean score for Group1 (M=39.21, SD=8.56) was significantly different from Group3 (M=43.69, SD=9.74). Considering Evaluative Concerns, the mean score for Group1 (M=39.86, SD=11.31) was significantly different from Group2 (M=46.91, SD=11.42) and from Group3 (M=51.75, SD=8.54).ConclusionsGPIU is consistently related to maladaptive perfectionism. Future longitudinal studies are needed to clarify the bidirectional association between GPIU and perfectionism traits.